2022
DOI: 10.3389/fmed.2022.841391
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of COL4A5 Splicing Variants to the Pathogenesis of X-Linked Alport Syndrome

Abstract: X-linked Alport syndrome (XLAS) is caused by pathogenic variants in COL4A5 and is characterized by progressive kidney disease, hearing loss, and ocular abnormalities. Recent advances in genetic analysis and further understanding of genotype-phenotype correlations in affected male patients raises the importance of detecting splicing variants in COL4A5. Aberrant splicing of COL4A5 is caused not only by canonical splice site variants but also non-canonical splice site variants such as deep intronic changes or eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…show that ASOs can induce exon skipping to alleviate the progression of Alport syndrome 70 . Exon 21 skipping resulted in the production of truncated functional protein that facilitated collagen re‐deposition and alleviated proteinuria in mice with the Col4α5 R471X mutation 70,77 . Daga et al.…”
Section: Current Therapeutic Status For Pediatric Genetic Kidney Dise...mentioning
confidence: 99%
See 1 more Smart Citation
“…show that ASOs can induce exon skipping to alleviate the progression of Alport syndrome 70 . Exon 21 skipping resulted in the production of truncated functional protein that facilitated collagen re‐deposition and alleviated proteinuria in mice with the Col4α5 R471X mutation 70,77 . Daga et al.…”
Section: Current Therapeutic Status For Pediatric Genetic Kidney Dise...mentioning
confidence: 99%
“…70 Exon 21 skipping resulted in the production of truncated functional protein that facilitated collagen re-deposition and alleviated proteinuria in mice with the Col4α5 R471X mutation. 70,77 Daga et al have reported using CRISPR/Cas9 for homologous recombination repair of mutation sites in patients' urinary podocytes in vitro, with a very high correction rate ranging from 44% in the COL4A3 gene to 58% in the COL4A5 gene, and a decrease in insertion-deletion percentage (10.4% for COL4A3 and 8.8% for COL4A5). 72 Lin et al have shown that specific induction of Col4α3 expression in podocytes of Col4α3 −/− mice can lead to the re-expression of the α3α4α5(IV) trimer and alleviate kidney dysfunction, prolonging the lifespan of mice.…”
Section: Current Therapies For Alport Syndromementioning
confidence: 99%
“…As in many heritable diseases, there is vast intraand inter-familial variability and allelic heterogeneity in the phenotypic expression of XLAS, such as in disease severity, onset age, and progression (5). In male XLAS patients, the genotype-phenotype correlation is evident; whereas patients with the nonsense variants show the most severe, early-onset ESRD phenotype, those with a splice variant and missense variant show moderate and mild phenotypes, respectively (6). A previous study reported that heterozygous female patients usually have a milder and more variable clinical course compared with male patients with XLAS (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, Whole-genome sequencing (WGS) not only comprehensively covers exons but also detects deep intronic and intergenic variations, but interpretation of non-coding variants via WGS is challenging. It has been shown that splice variants account for approximately 15% of all cases of XLAS (6). It was found significant differences in renal survival that are based on the abnormal splicing patterns of the COL4A5 primary transcript (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation